Methodology for Negotiation in Collaborative Working Environment for Innovation in Services Design - Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition (ASME IMECE 2014), 2014)
Service-oriented technologies drive new ways to perform interoperability between manufacturing companies. The aerospace segment is a highly competitive area, supported by numerous partners and applications which need to collaborate and to be interoperable. Particularly, the subcontracted small and medium enterprises (SMEs) need to be flexible towards the changes that are imposed by the major contractors, doing so at the lowest cost. This paper proposes a framework which advocates negotiations as a pillar mechanism to support innovation during the development of services in industrial collaborative working environments.